2015
DOI: 10.2298/jas1502159y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Wavit® rootstock with two plum and two apricot cultivars in nursery

Abstract: In order to expand the knowledge about the behavior of Wavit ® rootstock, we compared the growth characteristics which it induces on two plum and two apricot cultivars in nursery together with two commonly used rootstocks in Bulgaria for these species, Prunus cerasifera seedling and M29C. The study was conducted in the period 2012-2014 in a commercial nursery near Plovdiv. Plum cultivars Jojo and Cacanska Lepotica were T-budded on P. cerasifera seedling and Wavit ® rootstocks, and apricot cultivars Pricia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, "WaVit" is a rootstock selected from seedling populations of "Wangenheim" (P. domestica) with excellent uniformity. It reduces tree growth, induces early cropping, accelerates fruit ripening, and increases fruit size while producing high and regular yields [86,87].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, "WaVit" is a rootstock selected from seedling populations of "Wangenheim" (P. domestica) with excellent uniformity. It reduces tree growth, induces early cropping, accelerates fruit ripening, and increases fruit size while producing high and regular yields [86,87].…”
Section: Discussionmentioning
confidence: 99%
“…The rootstocks analyzed include 'Apricot seedling' (Prunus armeniaca L.), which is widely used in cultivation, and 'Fehér besztercei' (Prunus domestica L.), which is registered in the national variety register of Hungary (Hrotkó, 1999). 'Wavit' (Prunus domestica L.), derived from clonal lines of the Austrian Wangenheim plum, has been observed to reduce growth vigor in many cases (Yordanov et al, 2015). 'Wavit', similar to 'Fehér besztercei', is known for its uniform orchards and reduced vigor (Missere et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The final results, which were the means of four replicates for each experimental variant from one experiment, were expressed in mg of glucose per g of fresh Moreover, as reported by Sofla et al [14], other important objectives in apple breeding include adaptation to climatic conditions, tree growth habit and tree vigor, duration of juvenility and time of flowering. To ensure the greatest possible cropping, high and consistent yields of fruits uniform in size, shape and color for many years, fruit producers not only strive to improve tree training and orchard nutrition, but also use scion-rootstock combinations [39][40][41]. For example, Webster [42] reported that many rootstocks are used to propagate temperate fruit trees and improve tree vigor, beginning of fruit-bearing, tree productivity, fruit quality and adaptability to different environmental conditions.…”
Section: Determination Of Total Saccharide Contentmentioning
confidence: 99%